Development of Learning Media Based on Heyzine Flipbook in The Subject of Lathe Machining Techniques Class XI at SMK Kemala Bhayangkari 1 Jakarta - Berlian Ahmad Fauzi; C Rudy Prihantoro; Hari Din Nugraha (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
This research aims to develop and test the feasibility of products in the form of heyzine flipbook-based learning media in the subject of Lathe Machining Engineering class XI at SMK Kemala Bhayangkari 1 Jakarta. This learning media was developed using the R&D (Research and Development) method using a 4D model consisting of define, design, develop, and disseminate. In the process of assessing the feasibility of this learning media, it provides a validation assessment questionnaire instrument to material experts, media experts, and media feasibility tests to students in grade XI of Machining Engineering as respondents. Learning media is validated by experts with a score of 100% for the material aspect, 94% for the media aspect. And for the results of the feasibility trial, the learning media got a score of 91% of the results of the trial of 53 students. From the results of the test, it can be concluded that the heyzine flipbook-based learning media in the Lathe Machining Engineering class XI subject at SMK Kemala Bhayangkari 1 Jakarta is